Parenting is genetically influenced: What does that mean for research into child and adolescent social development? - Kretschmer, Tina (Social Development, 2023)
Individual differences in child and adolescent social development are due to a combination of variation in genetic propensity and environmental conditions. That is, variation in social domains like bullying-victimization, loneliness and pro- and antisocial behaviour is genetically influenced to a substantial extent. That is not to say that social contexts also do not play an important role in shaping social development. Indeed, parenting and parent–child relationship quality have been associated with various aspects of social development. What complicates matters is that environmental conditions – including parenting – are under genetic influence as well. Genetic influence on parenting has not received sufficient attention in the literature on social development although it likely biases estimates of parental effects on offspring social development. To change this situation, I review recent twin and molecular research on genetic influence on parenting and discuss why genetically-informed studies improve and enrich contemporary research into social development. The aim of this topic review is to provide an accessible introduction to genetics of parenting and encourage genetically-informed research into social development.
CRIS-Team Scopus Importer:2025-03-19
Keywords: genetic influence; parenting; polygenic scores; twin studies